2020
DOI: 10.1002/jcp.30095
|View full text |Cite|
|
Sign up to set email alerts
|

Maintenance and differentiation of human ES cells on polyvinylidene fluoride scaffolds immobilized with a vitronectin‐derived peptide

Abstract: Polyvinylidene fluoride (PVDF) is biocompatible, easy to fabricate, and has piezoelectric properties; it has been used for many biomedical applications including stem cell engineering. However, long‐term cultivation of human embryonic stem cells (hESCs) and their differentiation toward cardiac lineages on PVDF have not been investigated. Herein, PVDF nanoscaled membrane scaffolds were fabricated by electrospinning; a vitronectin‐derived peptide‐mussel adhesive protein fusion (VNm) was immobilized on the scaffo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…We tested Matrigel, recombinant VN (50 µg/mL), commercially available VN-derived peptide (VN XF ® from STEMCELL Technologies), VNP1, and VNP2 to determine whether these ECM molecules support oligodendrocyte differentiation from hPSC-derived OPCs. Another VN-derived peptide (VNm) was also included in the list because we have previously shown that it can support stable adherence and long-term culture of hPSCs [ 32 ]. OPCs were seeded on various matrices at the same density and induced to differentiate through SOX10 overexpression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We tested Matrigel, recombinant VN (50 µg/mL), commercially available VN-derived peptide (VN XF ® from STEMCELL Technologies), VNP1, and VNP2 to determine whether these ECM molecules support oligodendrocyte differentiation from hPSC-derived OPCs. Another VN-derived peptide (VNm) was also included in the list because we have previously shown that it can support stable adherence and long-term culture of hPSCs [ 32 ]. OPCs were seeded on various matrices at the same density and induced to differentiate through SOX10 overexpression.…”
Section: Resultsmentioning
confidence: 99%
“…To date, various ECM molecules have been identified for diverse biomedical applications, specifically to direct the differentiation of stem cells [ 44 ]. VN is one of the most widely used ECMs, particularly for hPSC engineering, because VN and VN-derived peptides are capable of maintaining hPSCs [ 16 , 45 ] and even facilitating their differentiation into specific cell types, including oligodendrocytes [ 32 ]. In this study, we to create a novel peptide derived from the VN peptide for the differentiation of oligodendrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Departing from improving the surface property for protein adhesion, directly introducing adhesive protein and signal molecules have also been proposed [173]. The human embryonic stem cells cultured on a nanofibrous PVDF web with vitronectin-derived peptide-mussel adhesive protein fusion coating were stably expanded for more than 10 passages, maintaining the expression of pluripotency markers and genomic integrity [174].…”
Section: Current Challenges and Solutionsmentioning
confidence: 99%
“…Piezoelectric materials have been shown to affect stem cell differentiation [ 11 , 12 ], as cells are able to sense the electrical stimuli provided by cyclic stretching/compression of the piezoelectric substrate. For example, electrical stimulation via piezoelectric materials led to a differentiation in neural stem cells [ 11 ], embryonic stem cells towards cardiomyocytes [ 13 ] and osteogenesis in mesenchymal stem cells [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%